Living on the edge in Leonardo's Florence : selected essays - Brucker, Gene A. (University of California Press, 2005)
In Living on the Edge in Leonardo's Florence, an internationally renowned master of the historian's craft provides a splendid overview of Italian history from the Black Death to the rise of the Medici in 1434 and beyond into the early modern period. Gene Brucker explores those pivotal years in Florence and ranges over northern Italy, with forays into the histories of Genoa, Milan, and Venice. The ten essays, three of which have never before been published, exhibit Brucker's graceful intelligence, his command of the archival sources, and his ability to make history accessible to anyone interest.